Citizens' views on lifelong learning in the 10 new Member States : report based on the special Eurobarometer 231 - (:unkn) unknown (Office for Official Publications of the European Communities, 2008)
"The 2005 lifelong learning Eurobarometer maps the subjective views of citizens aged 15+ in the 10 new Member States that joined the European Union in May 2004. This report provides a detailed analysis of the survey results that reflect attitudes and behaviour towards lifelong learning from individuals own assessment and statements.The analysis aims at considering results of other relevant data sources and research studies that cover lifelong learning related issues. The results of the 2005 Eurobarometer confirm and extend the principal knowledge about lifelong learning from other such surveys and empirical studies. They also provide new and interesting facts and aspects on popular beliefs on the usefulness of lifelong learning and of different skills, on learning preferences and motivation to take up learning in the course of life." (Hrsg.)
Keywords: S 1.5.2 Berufliche Weiterbildung; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; T 3.4 Befragung; G 1.3.2 Bildungsverhalten und -verläufe; G 2.4.2 Lebenskonzepte, -stile, Werte; I 2.2.2 Osteuropa; Berufliche Weiterbildung; Lebenslanges Lernen; Befragung; Weiterbildungsverhalten; Weiterbildungsbereitschaft; Gesellschaftliche Einstellung; Osteuropa; Quantitative Angaben; 2005